Implikasi Tumpang Tindihnya Pasal Ujaran Kebencian Pada Tahap Prapenuntutan Perspektif Sistem Peradilan Pidana Indonesia - M. Ilham Wira Pratama (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
The criminal justice system aims to enforce material criminal law and formal criminal law. The parts in a legal system in principle should not be in conflict, conflict, or overlap with each other. However, the offense of expressing hatred is regulated in more than one criminal law legislation (overlapping) so that this has the potential to affect the law enforcement process in the criminal justice system. So it is necessary to know what the implications are in the criminal justice system, especially at the pre-prosecution stage. The research is a normative legal research with a statutory and conceptual approach. The results of the study indicate that the overlapping provisions of criminal law regarding hate speech have implications for the stagnation of the case process at the pre-prosecution stage, because of the potential for back and forth case files between investigators and public prosecutors because both of them can have different opinions and stances regarding the hate speech article that will be applied, so as to be detrimental to the suspect's right to obtain legal certainty and the quick and simple judicial process will be neglected.